Kennesaw State University: Collaborative Clinical Practice - Heckert, Jennifer; Strieker, Toni; Shaheen, Maria (Educational (Re)naissance, 2013)
As teacher educators in the United States, our capacity to prepare competent P-12 educators who are ready to meet the challenges of 21st century schooling has been called into question (Darling-Hammond, 2006). Low student achievement and high teacher attrition rates have resulted in a national call to prepare prospective and practicing teachers with the knowledge, skills, and dispositions to collaborate with colleagues and to provide an equitable and quality education for all students, particularly those from diverse backgrounds (Darling-Hammond, 2010). For example, the NCATE Blue Ribbon Panel on Clinical Preparation and Partnerships for Improved Student Learning (2010) recommends the transformation of clinical practice in order to better prepare prospective and practicing teacher with programs that create opportunities: (a) for partnerships with schools to advance shared responsibility for teacher preparation; (b) for prospective teachers to learn by doing; (c) for transforming curriculum, pedagogy, structure and delivery; and (d) to ensure prospective teachers will know how to collaborate with colleagues.